2020
DOI: 10.1139/cjfas-2019-0350
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive trade-offs in fish energetics and physiology: insights from adaptive differentiation among juvenile salmonids

Abstract: Juveniles of different salmonid species often co-exist along environmental gradients, making them a useful model for identifying dominant trade-off axes and their stability within a biological hierarchy (e.g., from individuals to populations to species). In this perspective, we use multivariate trade-offs among juvenile coho salmon (Oncorhynchus kisutch) and rainbow trout (Oncorhynchus mykiss) as a case study to explore broader-scale patterns of trait association. Multivariate ordination identified a dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 157 publications
0
27
0
Order By: Relevance
“…For instance, recent studies observed a positive covariance between growth and swimming capacity (i.e. U crit , MMR, AS) in steelhead (Rosenfeld et al., 2020; Van Leeuwen et al., 2011), and a positive correlation between aerobic scope and maximum FC in brown trout (Auer, Salin, Anderson, & Metcalfe, 2015). Collectively, these contrasting outcomes suggest that metabolic trade‐offs may be highly context‐specific (Careau & Garland Jr., 2012; Careau, Killen, & Metcalfe, 2014), with local idiosyncrasies in ecological and evolutionary context driving variability in trait associations that underlie adaptive differentiation of populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, recent studies observed a positive covariance between growth and swimming capacity (i.e. U crit , MMR, AS) in steelhead (Rosenfeld et al., 2020; Van Leeuwen et al., 2011), and a positive correlation between aerobic scope and maximum FC in brown trout (Auer, Salin, Anderson, & Metcalfe, 2015). Collectively, these contrasting outcomes suggest that metabolic trade‐offs may be highly context‐specific (Careau & Garland Jr., 2012; Careau, Killen, & Metcalfe, 2014), with local idiosyncrasies in ecological and evolutionary context driving variability in trait associations that underlie adaptive differentiation of populations.…”
Section: Discussionmentioning
confidence: 99%
“…SMR) and potentially reduce energy allocation towards organs involved in oxygen intake and delivery, thus lowering aerobic potential. Metabolic trade‐offs are common in vertebrates, ranging from mice (Sadowska, Gebczynski, & Konarzewski, 2013) to juvenile salmonids (Rosenfeld, Richards, Allen, Van Leeuwen, & Monnet, 2020; Van Leeuwen et al., 2011). However, many populations that demonstrate this growth versus active metabolism trade‐off are artificially selected for fast growth, (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Under high food availability, a high SMR in combination with high AS can increase growth rate (Auer et al 2015c), as it often correlates with traits that improve resource acquisition, such as dominance and digestive capacity Mathot et al 2019;Rosenfeld et al 2020). Under low food availability, the growth benefit of high SMR or AS can be minimized (or even reversed for SMR) due to high self-maintenance costs (Auer et al 2015c;Zeng et al 2017;Auer et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Early maturation depends on faster growth and fat deposition compared to late maturation in the freshwater (juvenile) and early marine phase (Skilbrei 1989;Salminen 1997;Hutchings & Jones 1998;Tréhin et al 2021). This suggests that early maturation in salmonids may be associated with higher SMR or aerobic scope via resource utilization (Mathot et al 2019;Rosenfeld et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…More generally, salmon exploit habitat heterogeneity (e.g., temperature, prey availability; Armstrong et al 2010), a system‐level trait that emerges in large, intact systems. Growth in particular can shift from positive to negative with a gradual increase in temperature (Brett 1971) and salmon can employ fine‐scale, adaptative feeding strategies given their metabolic requirements (e.g., Rosenfeld et al 2020), but this requires adequate distributions of food and temperature resources underpinned by habitat complexity at larger scales. Thus, broad‐scale habitat simplification may reach thresholds beyond which conditions at the system level more readily transition between desirable and undesirable states.…”
Section: Potential Management Applications Of Leveraging Nonlinearitimentioning
confidence: 99%